SIMULATION AND EXPERIMENTAL INVESTIGATION OF A COUPLED-INDUCTOR BASED LED DRIVER CIRCUIT (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2026)
A light-emitting diode (LED) or an LED string can receive a regulated power input from highly efficient, low-cost LED driver topologies using a simple control strategy. The presented work elucidates the analysis of a DC-DC buck topology-based single-stage LED driver circuit with dual output voltage levels. The projected driver structure has a reduced semiconductor-based component count and can control the LED light output. The suggested driver circuit employs a magnetically coupled inductor for transformerless energy transfer. The power switches employed in the proposed structure use a zero-voltage switching (ZVS) strategy to prevent voltage transients that may occur during switch turn-off due to leakage flux components of the inductors. The control and regulation of the light output of the LED lamps are achieved by applying double Pulse Width Modulation (PWM) signals to the switches. The proposed topology features relatively low power losses and improved voltage regulation. The simulation analysis and the projected driver-circuit results obtained in PSIM 9.0 are validated against prototype model results.
Keywords: DC-DC buck topology; Double pulse width modulation (PWM) technique; Light-emitting diode (LED) driver circuit; PSIM; Zero-voltage switching (ZVS)